An Empirical Research for Identifying and Analyzing the Identity Characteristics of Different Online Destination Websites - Briciu, Victor-Alexandru; Briciu, Arabela; Gulpe, Ana-Maria (LUMEN Proceedings, 2019)
The online environment and the other digital media have revolutionized human interaction. This is the network effect that organizations must use to reach their goals, and the destinations management organizations are also included in finding better solutions for promoting, communicating and marketing the desired place. This online presence of billions of people can be used both in organizational communication activities and in other areas, for research or facilitating professional activities. In this light, the research objective is to identify the Internet usage from the managerial point of view, i.e., the destination branding management of websites. The research study will try to specify and analyse the main features of destinations websites or the principal dimensions of their online identity, by applying a content analysis method scheme on 10 selected destination websites. Findings from the study suggest that the Web 1.0 paradigm is still being used or promoted, rather than the participatory Web 2.0, that nowadays is associated with a large range of tools and software used for viewing and developing the websites, allowing the users to interact directly with any web content in order to obtain custom rewards. Changes are taken into consideration by the destinations management organizations in terms of transmitting the information with greater visibility to targeted audiences. The online environment is, therefore, in favour of any organization that wants to be connected to this world of technology and professionalism.